2014
DOI: 10.1093/ndt/gfu185
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease rather than illness severity predicts medium- to long-term mortality and renal outcome after acute kidney injury

Abstract: In an unselected series of patients with AKI requiring RRT, underlying CKD rather than illness severity predicted medium- to long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
2
7
1
Order By: Relevance
“…Notably, poor pre-morbid functional status and presence of malignancy were strongly associated with decreased survival at 3 years. Our results corroborate a Scottish study that found underlying CKD among patients commenced RRT to predict long-term mortality rather than severity of acute illness [25]. Finally, our results were robust to excluding patients with pre-existing CKD, those with estimated baseline Cr, and those AKI patients who did not receive RRT.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, poor pre-morbid functional status and presence of malignancy were strongly associated with decreased survival at 3 years. Our results corroborate a Scottish study that found underlying CKD among patients commenced RRT to predict long-term mortality rather than severity of acute illness [25]. Finally, our results were robust to excluding patients with pre-existing CKD, those with estimated baseline Cr, and those AKI patients who did not receive RRT.…”
Section: Discussionsupporting
confidence: 88%
“…Findlayet al further examined the information of patient with renal replacement therapy requiring AKI in Southwest Scotland between 1994 and 2005. The data from this study indicate that the underlying CKD rather than illness severity can predict the medium- to long-term mortality 30 . Macedoet al followed 84 adult survivors of AKI for a median time of 4.1 years and showed that age and serum creatinine levels at hospital discharge were independent factors associated with non-recovery of renal function 31 .…”
Section: The Aki-ckd Connectionmentioning
confidence: 75%
“…Either in terms of disease severity or mortality, we found that CKD unfavorably impacted the COVID-19 infection. Fourth, preexisting CKD is a significant risk factor for worsening of kidney function during a severe infection (71,72). Once complicated by AKI, CKD itself was associated with a higher risk of mortality and less chance of kidney recovery (73).…”
Section: Discussionmentioning
confidence: 99%